Effects of live feed manipulation with algal‐derived antimicrobial metabolites on fish larvae microbiome assembly: A molecular‐based assessment. (10th November 2021) - Sanches‐Fernandes, Gracinda M. M.; Califano, Gianmaria; Castanho, Sara; Soares, Florbela; Ribeiro, Laura; Pousão‐Ferreira, Pedro; Mata, Leonardo; Costa, Rodrigo
Abstract: Opportunistic microorganisms acquired through rearing water or live feed ingestion are believed to underpin high mortality rates of fish larvae, constituting a production bottleneck for the aquaculture industry. We employed 16S rRNA gene sequencing to determine whether treatment of live feed (rotifers and Artemia ) with algal‐derived, antibacterial metabolites could alter bacterial community structure of gilthead seabream ( Sparus aurata ) larvae in a larviculture facility. Owing to a large degree of sample‐to‐sample variation, pronounced 'legacy effects' of live feed manipulation on the total fish larvae bacterial community could not be verified. Notwithstanding, the approach induced shifts in relative abundance of specific bacterial phylotypes in both the live feed and fish larvae. Some phylotypes representing opportunistic taxa such as Stenotrophomonas, Pseudomonas and Klebsiella displayed reduced abundances in the bacterial community of fish larvae fed metabolite‐treated vs. control live feed. Conversely, potentially beneficial phylotypes in the Alphaproteobacteria clade were consistently—although not significantly—promoted in the treated larval samples. These outcomes encourage future microbiome manipulation attempts to improve fish larviculture. However, successful host colonization and competition with resident symbionts are primary barriers that need to be overcome if live feeds are to be used as effective delivery systems of beneficial bacteria to fish larvae.